Formation of system of support of development of small youth business - L. G. Rudenko (Вестник университета, 2019)
The results of the research of youth entrepreneurship problems have been adduced. Institutions and programs of its support have been considered. Measures to eliminate the identified problems of attracting young people to entrepreneurship have been recommended. The formation of a new program of support «Acceleration of youth entrepreneurship» and the creation of coordination centers in the subjects of the Russian Federation «Regional youth center» have been off red. The model of the system of support of small youth entrepreneurship, which will increase entrepreneurial activity among young people and create new jobs, has been presented.